Effect of Different Salt Concentrations on Germination and Shoot Development in Pre-treated Alfalfa (Medicago sativa L.) Seeds - ÖTEN, Mehmet; KUÇİN, Beyza (MAS Journal of Applied Sciences, 2024)
One of the most important factors in the decrease in usable agricultural areas today is the salinity problem. The salinity problem negatively affects the development of many plants, especially alfalfa, during the germination phase and even causes plant deaths. In recent studies, this problem has been solved by pre-treatment of seeds. This research was conducted with three replications in the Laboratory of the Faculty of Agriculture at Sakarya Applied Sciences University. The "Beyzade" variety of clover was used, and growth regulators sold in the market as Panoramix, Kerotin-L, Avesis root, and Momentum Plus were applied as pre-treatments. Subsequently, commercial fungicides such as Metaxyl, used against soil-borne pathogens, were added. Seeds were coated with corn starch and molasses and covered with ash and clay. Four different salinity stress levels (0, 1.5, 3, 4.5, 6 ds/m) were applied during the germination period. Various characteristics such as germination rate (%), germination power (%), root length (mm), stem length (mm), root fresh weight (g), root dry weight (g), stem fresh weight (g), stem dry weight (g), salt tolerance index and vigor index were examined in the study. The results indicated that increasing salt concentration adversely affected the examined characteristics. However, the pre-treatments were found to create tolerance in seeds against the increasing salinity doses.